MULTI-PURPOSE OPTIMIZATION OF THE PRODUCT RELEASE PROGRAM - D. A. Alferev; A. E. Kremin (Вестник университета, 2020)
A model of the optimal production plan of an industrial enterprise, formalizing its production program has been presented. An example of its solution by minimizing the maximum permissible cumulative deviation from optimal production plans, drawn up with a single local target optimization criterion has been adduced. The modeling of variability in the preparation of the production program and the selection from possible scenarios of those, which can actually be successfully implemented, has been analyzed by example. In addition to the method described above, two more options have been proposed for optimizing the program, which can be considered as alternative ways to solve the existing problem, or as additional scenarios for the development of events. The results of this work will be useful to persons, involved in the rational and effective management of industrial production systems.